Beyond Open Doors and Performative Allyship: A Subaltern Autoethnographic Account on ‘White’ Allyship in the Post-2020 BLM Protests Era (London Journal of Research In Management & Business, 2024)
The COVID-19 Pandemic brought to light the racial inequities in the United Kingdom through its disproportionate impact on racialised minority communities. The murder of George Floyd in the hands of people who should have been protecting him reinvigorated the Black Lives Matter (BLM) social movement in the United States of America (USA). Inspired by social media reports and engagements, BLM messages were appropriated and adopted in many countriesacross the world, including the United Kingdom (UK). The BLM protests in the UK, on the one hand, highlighted the racial inequalities in the UK and reminded the public of the UK's colonial history.It is not surprising that the BLM protests led corporate entities, foundations and even churches in the UK to commission inquiries to explore their history and potential connections to colonialism, slavery, and indentured labour. Many would later issue statements and commit to investing in initiatives to address racial inequalities. These institutions stated that they were shifting from standing against racism to becoming antiracist. In effect, they were committing to becoming allies in promoting racial equity and addressing the structural challenges standing in the way of racial equity. Allyship is not a new concept; literature has covered allyship polarities ranging from performative to authentic/substantive allyships.The paper is informed by The Open University's Centre for Voluntary Sector Leadership's research on collaboration and engagement between the leadership of racialised minority networks and service providers in promoting racial equity. The research is complemented by my lived experience as a racialised minority leader engaged in social and political practices geared towards addressing racial inequities. This autoethnographic paper seeks to explore whether, four years after George Floyd's murder, approaches to allyship have changed to embody the commitment to antiracist practices on the one hand and a move away from tokenism and promote emancipatory allyship.
Keywords: COVID-19; Pandemic; Malaysia; Youth; Cashless transaction; e-transaction; cashless economy; online transaction; Allyship; Autoethnography; Emancipatory; Performative; Substantive; Symbolic; Vacuous